Perancangan Komunikasi Visual CT-Eats Jasa Transportasi Online Caktrans Dengan Teknik Vector Untuk Memperluas Segmentasi Pasar - Mustakim, Wilyan; Bahruddin, Muh; Yurisma, Dhika Yuan (Jurnal Art Nouveau, 2016)
The purpose of visual communication design is to introduce food delivery service program by Caktrans, online transportation services. More research is conducted by using qualitative method which is interview, observation, documentation, and literacy in order to get the data that support the creation of CT-Eats visual communication concept by Caktrans. Analytical data used a few steps, those are data reduction, data presentment, and conclution. After the data is analyzed, the we found the design concept or the keyword of visual communication design, that is “dedicated”. Description of “dedication” is a form of service dedication given by CT-Eats, Caktrans. The purpose it self, to create the sincerity and socialbility, of CT-Eats service. “Dedicated” concept, hope fully could be food delivery service who can be dedicate or present the great services to all costumer. Could give satisfaction to costumer in the service of hard work, comfort, and friendliness. Therefore, the “dedicated” concept is a view of service dedication by CT-Eats, Caktrans. Keyword : Visual Communication, Visual Merchandise, Online Transportation Services, CT-Eats.